ARTIFICIAL INTELLIGENCE BETWEEN STRATEGIC CULTURE AND GLOBALIZATION (Heritage, 2025)
The paper explores the complex interactions between strategic culture, globalization and the development of artificial intelligence and their role in national security. One of the key aspects that stands out is the need for adaptability in response to these new challenges. Globalization and artificial intelligence are changing the landscape of national security, affecting the way states consider and respond to various threats. There is a need for flexibility and adaptability both at the strategic level and in the context of political action in order to adequately respond to contemporary challenges in the field of security. Advances in artificial intelligence require states to quickly react and adapt to new opportunities, but also challenges. This includes the development of standards and legal regulations that will ensure the ethical, legal and safe application of artificial intelligence in the context of national security.Additionally, adaptability is essential in developing strategies to counter new security threats arising from globalization. The process of globalization may bring new challenges, such as transnational terrorism and cyber threats, which require a coordinated response and cooperation at the international level. An appropriate national security strategy must be able to rapidly adapt to these new challenges and incorporate new technologies and approaches, including artificial intelligence. Also, adaptability is important in the context of developing a strategy for the adoption of artificial intelligence in the domain of national security. This includes the training and education of professionals, the development of new skills and capacities, as well as the constant updating and refinement of safety management strategies and techniques. Only through an adaptable and flexible approach is it possible to successfully face the new and complex challenges brought by globalization and the development of artificial intelligence.
Keywords: strategic culture, globalization, artificial intelligence, new dimensions of national security, adaptability.